2013
DOI: 10.3390/ijms141020564
|View full text |Cite
|
Sign up to set email alerts
|

Erucin Exerts Anti-Inflammatory Properties in Murine Macrophages and Mouse Skin: Possible Mediation through the Inhibition of NFκB Signaling

Abstract: Erucin, an isothiocyanate, is a hydrolysis product of glucoerucin found in arugula and has recently been reported to have anti-cancer properties in various cancer cells. In this study, we assessed the anti-inflammatory effects of erucin and the underlying mechanisms, using lipopolysaccharide (LPS)-stimulated RAW 264.7 murine macrophages and 12-O-tetradecanoylphorbol-13-acetate-treated mouse skin. In RAW 264.7 cells, erucin (2.5, 5 μmol/L) inhibited LPS-induced production of nitric oxide and prostaglandin E2. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Also, ITCs have been linked with lower cancer risk [74,75] via suppressing NF-κB signalling pathways that lead to attenuated pro-inflammatory mediators and activities. ITCs were shown to reduce several pro-inflammatory mediators and cytokines, including iNOS, apparently by downregulation of NF-κB signalling pathways [74,76].…”
Section: Discussionmentioning
confidence: 99%
“…Also, ITCs have been linked with lower cancer risk [74,75] via suppressing NF-κB signalling pathways that lead to attenuated pro-inflammatory mediators and activities. ITCs were shown to reduce several pro-inflammatory mediators and cytokines, including iNOS, apparently by downregulation of NF-κB signalling pathways [74,76].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB, a critical transcription factor that is involved in the inflammatory response, controls the expression of various compounds such as IL-6, IL-1β, TNF-α, iNOS, and COX-2 (Cho et al, 2013). In this study, mRNA expression of NF-κB p65 significantly declined during the entire duration of the trial ( Figure 3 ) and the lowest expression was recorded in the S220 group at 14 dpa.…”
Section: Discussionmentioning
confidence: 99%
“…Following activation, NF-κB translocates to the nucleus and induces target gene transcription, so as to regulate the synthesis of cytokines and other inflammatory factors (23). Studies have confirmed that NF-κB has extensive biological effects, plays a significant role in the regulation of inflammation, and is a key link in the complex network of inflammatory cytokines (24,25). Moreover, it modulates the occurrence and development of inflammation.…”
Section: Discussionmentioning
confidence: 99%